2021
DOI: 10.21659/rupkatha.v13n4.54
|View full text |Cite
|
Sign up to set email alerts
|

Master Students’ Perceptions of Blended Learning in the Process of Studying English during COVID 19 Pandemic in Ukraine

Abstract: The academic year 2020/2021 in higher education institutions in Ukraine began under the conditions of deteriorating epidemiological situation caused by the spread of Covid-19 pandemic. Students’ training was recommended to be carried out in the form of distance learning or blended learning. This research aims to analyse Master students’ perceptions of blended learning in the process of studying English in higher education institutions. The study presents the integrated course “Foreign Language for Specific Pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…To get the data of students perception in using B-leaning in post covid, the researcher used the questionnaire which adopted from (Bezliudna et al, 2021). The questionnaire has been used in their research and already calculated for the validity.…”
Section: Methodsmentioning
confidence: 99%
“…To get the data of students perception in using B-leaning in post covid, the researcher used the questionnaire which adopted from (Bezliudna et al, 2021). The questionnaire has been used in their research and already calculated for the validity.…”
Section: Methodsmentioning
confidence: 99%
“…Individually, the students highlighted the flexibility they had with BL to organize their time and follow the pace of study that best suited them [17,18,21]. In particular, the fact that they did not have to travel to the university for classes saved them time that they invested in studying or in other activities.…”
Section: Covid-19 Periodmentioning
confidence: 99%
“…Many students perceived that BL made it difficult for them to adequately demonstrate their knowledge. This was because the students did not have the necessary training to handle and solve the problems using the different tools, generating in them the assumption that they did not show an adequate performance [21].…”
Section: Covid-19 Periodmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no studies have been found that analyse BL using an experientially oriented approach (focusing on the student as a customer) and, even more importantly, that analyse the relationships that the concepts of experience, satisfaction and commitment have with each other. It is known, in particular, that BL can improve student performance [3] or be satisfactory [4]. Nevertheless, the impact of BL on student commitment through satisfaction, which is considered an intermediate outcome of the student experience and leads to student commitment, has not been studied, least of all during a pandemic period.…”
Section: Introductionmentioning
confidence: 99%